Theory, research and clinical applications of self-control - Montgomery urday, William (2008)
It examines the role of self-control in its variety of meanings and applications, from experimentation to clinical behavior. It is emphasized that behavioral repertoires of selfcontrol in an individual are learned, which reinforces the need to promote learning in psychotherapeutic situation through structured procedures for doing so, such as therapies for management of anxiety and anger, assertiveness, covert conditioning, rational restructuring, problem solving, autoinstruccional training, and biofeedback, propitiating through development of such procedures the self-monitoring and relaxation, coping skills, and specific changes in lifestyle.